Storytelling and Emotional Resilience: A Narrative Analysis of Mental Health Interventions in Primary Schools - Siti Masitoh; Rika Fitriyana (International Journal of Educational Narratives, 2025)
Background. The rising prevalence of mental health challenges among primary school children necessitates the exploration of accessible and effective school-based interventions. Storytelling, a pedagogical tool deeply embedded in childhood, presents a promising, culturally-sensitive medium for fostering emotional resilience. However, empirical analysis of its specific contribution to resilience-building within structured mental health programs remains underexplored. Purpose. This study aimed to analyze how children’s narratives, developed through a storytelling-based mental health intervention, reflect the cultivation of emotional resilience. Methods. Employing a narrative analysis framework, this qualitative study examined the stories created by 30 children aged 8-10 participating in a 12-week intervention program. Data were collected from recorded storytelling sessions and the children’s written and illustrated narratives. The analysis focused on identifying recurring themes, character arcs, and plot resolutions indicative of resilience strategies. Results. The analysis revealed that children’s narratives progressively incorporated themes of overcoming adversity, seeking social support, and positive self-talk. Characters in their stories demonstrated increased agency and problem-solving skills, shifting from narratives of distress to narratives of hope and coping. Conclusion. Storytelling interventions provide a powerful platform for children to articulate, process, and integrate concepts of emotional resilience. The narrative process enables the externalization of internal struggles and the rehearsal of adaptive coping mechanisms, positioning storytelling as a valuable component of primary school mental health support.